PROMOTING SELF-REFLECTION THROUGH POSITIVE TEACHER’S CAMP - Yofrina Octika Gultom (Adisam Publisher, 2025)
Promoting self-reflection among teachers is crucial for fostering personal and professional growth. The Positive Teacher’s Camp in Indonesia provides a platform for teachers to engage in reflective teaching practices and establish connections among teachers. This camp was organized by Generasi Cerdas Indonesia (GCI) and Initiatives of Change (IofC) Indonesia. The camp agenda includes self-reflection exercises, plenary sessions, workshops, and guided discussions, all aimed at creating a safe and supportive environment for teachers to evaluate their teaching methods and students' approach. Participants are encouraged to evaluate their performance, identify areas for improvement, and integrate regular self-reflection into their teaching practice. This paper aims to promote the importance of self-reflection in education, empowering teachers for personal and professional development. This study used the qualitative descriptive methodology to present a clear and comprehensive overview of the camp. This approach seeks to directly describe phenomena by observing the camp to gather firsthand data on its conduct and the topics discussed. In conclusion, the Positive Teacher’s Camp plays a crucial role in nurturing the personal and professional growth of teachers, leading to improved educational outcomes for students by fostering a culture of continuous improvement and development, including practice of regular self-reflection in teaching learning process